Epigenetic Memory Emerging from Integrated Transcription Bursts - Kurz, Volker (The Biophysical Society, 2013)
Some autonomous bacteria coordinate their actions using quorum-sensing (QS) signals to affect gene expression. However, noise in the gene environment can compromise the cellular response. By exercising precise control over a cell’s genes and its microenvironment, we have studied the key positive autoregulation element by which the lux QS system integrates noisy signals into an epigenetic memory. We observed transcriptional bursting of the lux receptor in cells stimulated by near-threshold levels of QS ligand. The bursts are integrated over time into an epigenetic memory that confers enhanced sensitivity to the ligand. An emergent property of the system is manifested in pattern formation among phenotypes within a chemical gradient.